PENGARUH KUALITAS PELAKSANAAN CORPORATE GOVERNANCE DAN KOMPLEKSITAS BANK TERHADAP FRAUD (Studi Kasus Pada Bank Umum Tahun 2010) - Maya Indriastuti; Luluk M. Ifada (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
The purpose of this study was to investigate influence the quality of the implementation of Corporate Governance (CG) and the complexity of the bank against fraud in commercial banks in 2009. Dependent vaty of bank CG. The main issues discussed in this study is the number of occurrences of fraud on the bank caused by the poor quality of execution of CG / not good. To test the above issues, conducted research on the quality and complexity of the CG implementation of bank fraud that occurred at commercial banks in 2010. Theoretical framework and data analysis performed using multiple regression with least squares equation and hypothesis testing using the t-statistic for testing the partial regression coefficients and the f-statistic to test the influence keberartian together with the level of significance of 5%. Moreover, also tested the classical assumptions include normality test, test multicollinearity, heteroskedastisitas test and autocorrelation test. The results of the analysis indicate that the variable quality of execution of CG proven negative effect on the fraud at the level of significance of less than 5% while the complexity of the bank proved to be positively related to fraud at the level of significance of 5%.Keywords : Corporate Governance, fraud, complexity of the bank